Awareness of heart failure, blood pressure management and self-efficacy: The Research Goes Red for Women Registry - Katherine M Conners; Maryam Hashemian; Claire Kinzy; Jennifer L Hall; Christine Herr; Reeti Sharma; Pratheek Mallya; Juan Zhao; Nasrien E Ibrahim; Joseph J Shearer; Haoyun Hong; Véronique L Roger (Women's Health)
Background: Heart failure (HF) is increasing in the United States, and awareness is needed for prevention. Hypertension is the leading cause of HF, and adherence to antihypertensive medication is critical for reducing HF risk. Self-efficacy positively influences health-promoting behaviors. Objectives: Assess HF awareness, test associations with antihypertensive medication adherence, and self-efficacy for managing chronic conditions. Design: We conducted a cross-sectional, observational survey research study. Methods: We leveraged data from participants enrolled in the American Heart Association’s Research Goes Red™ registry, an online platform powered by Verily. Three surveys ascertained HF awareness, blood pressure management, and self-efficacy. Chi-squared and Wilcoxon rank sum determined associations between survey domains and participant characteristics. Results: Two thousand three hundred twenty women took the HF awareness survey, 678 the blood pressure management survey, and 755 the self-efficacy survey (response rates: 12%, 78%, and 76%, respectively). Participants were predominantly non-Hispanic White (78%), with a median age of 51 (interquartile range (IQR): 39, 62). Median HF awareness score was 4/5 (IQR: 4, 5). Participants with high HF awareness versus low were more likely to be older ( p  < 0.001), non-Hispanic White ( p  < 0.001), and less likely to smoke ( p  < 0.001) or have depression ( p  = 0.004). Nearly 90% of hypertensive participants reported medication adherence, which was not associated with HF awareness or self-efficacy. Participants with greater self-efficacy versus less were more likely to have higher HF awareness ( p  = 0.01), be older ( p  = 0.01), and less likely to have depression ( p  < 0.001). Conclusion: Women’s awareness of HF and adherence to antihypertensive medication in this cohort was high. Depression and younger age may be important factors affecting women’s HF awareness and confidence in managing chronic disease medication plans.